YAP/Smad3 promotes pathological extracellular matrix microenviroment‐induced bladder smooth muscle proliferation in bladder fibrosis progression - Xing‐Peng Di; Xi Jin; Jian‐Zhong Ai; Li‐Yuan Xiang; Xiao‐Shuai Gao; Kai‐Wen Xiao; Hong Li; De‐Yi Luo; Kun‐Jie Wang (MedComm)
Abstract Fibrosis is a chronic inflammation process with excess extracellular matrix (ECM) deposition that cannot be reversed. Patients suffer from bladder dysfunction caused by bladder fibrosis. Moreover, the interactive mechanisms between ECM and bladder fibrosis are still obscure. Hence, we assessed the pivotal effect of Yes‐associated protein (YAP) on the proliferation of bladder smooth muscle in fibrosis process. We identified that stiff ECM increased the expression and translocation of YAP in the nucleus of human bladder smooth muscle cell (hBdSMC). Sequencings and proteomics revealed that YAP bound to Smad3 and promoted the proliferation of hBdSMC via MAPK/ERK signaling pathway in stiff ECM. Moreover, CUT and TAG sequencing and dual‐luciferase assays demonstrated that Smad3 inhibited the transcription of JUN. The YAP inhibitor CA3 was used in a partial bladder outlet obstruction (pBOO) rat model. The results showed that CA3 attenuated bladder smooth muscle proliferation. Collectively, YAP binding with Smad3 in the nucleus inhibited the transcription of JUN, and promoted the proliferation of bladder smooth muscle through the MAPK/ERK signaling pathway. The current study identified a novel mechanism of mechanical force induced bladder fibrosis that provided insights in YAP‐associated organ fibrosis.